A Novel Mutation of the CYP11B2 in a Saudi Infant with Primary Hypoaldosteronism - Lama Alfaraidi; Abrar Alfaifi; Rawan Alquaiz; Faten Almijmaj; Horia Mawlawi (Case Reports in Endocrinology)
Isolated hypoaldosteronism is a rare autosomal recessive disease presenting with severe salt wasting and failure to thrive in infancy. A 6-month-old Saudi girl born to consanguineous parents was referred from primary health care for failure to thrive and developmental delay. Laboratory tests revealed hyponatremia, hyperkalemia, and metabolic acidosis with high renin and low aldosterone. Blood samples were collected for endocrine and genetic studies. Sequence analysis of the CYP11B2 revealed a T to A transition at position 1398 + 2 in exon 8 of the gene in a homozygous state (c.1398+T>A). This result was confirmed by sequencing an independent PCR product. Given the position of the transition at a highly conserved nucleotide and the predictions of different bioinformatic algorithms, it is likely that the mutation is the pathogenic cause of this condition. This result was compared with the reference NM_000498.3. Here, we report a novel homozygous mutation resulting in aldosterone synthase deficiency. To the best of our knowledge, this mutation has not been described in the literature or in any database thus far. The mutation manifested as a rare inherited disease in an infant exhibiting critical salt loss. An adequate replacement treatment will give a good long-term prognosis.